Corporate Financial Structure and Financial Stability - Stone, Mark (IMF Working Papers; Working Paper ;, 2004)
This paper uses flow-of-funds and balance sheet data to analyze the impact of financial crises on corporate financing and GDP in a range of countries. Post-crisis GDP contractions are mainly accounted for by declines in investment and inventory and are more severe for emerging market countries. Post-crisis investment and inventory declines are correlated with the corporate debtequity ratio. Although companies in emerging market countries hold more liquidity, this is not sufficient to prevent a greater response of expenditures to shocks. Industrial countries appear to benefit from an offsetting increase in bond issuance.